HACKATHON IS A POWERFUL TOOL FOR UNLEASHING THE POTENTIAL OF THE NEW GENERATION OF YOUNG PEOPLE - Негруб, Світлана; Бончук, Світлана; Негруб, Михайло (SWorldJournal, 2025)
The paper discusses the practical experience of the teaching staff in organizing and conducting a HACKATHON with the participation of high school students and higher education students of various specialties. While working on the project, the team learne